Loss of chromosome Y leads to down regulation of KDM5D and KDM6C epigenetic modifiers in clear cell renal cell carcinoma - Arseneault, Madeleine; Monlong, Jean; Vasudev, Naveen S.; Laskar, Ruhina S.; Safisamghabadi, Maryam; Harnden, Patricia; Egevad, Lars; Nourbehesht, Nazanin; Panichnantakul, Pudchalaluck; Holcatova, Ivana; Brisuda, Antonin; Janout, Vladimir; et al. (Scientific reports, 2017)
Recent genomic studies of sporadic clear cell renal cell carcinoma (ccRCC) have uncovered novel driver genes and pathways. Given the unequal incidence rates among men and women (male:female incidence ratio approaches 2:1), we compared the genome-wide distribution of the chromosomal abnormalities in both sexes. We observed a higher frequency for the somatic recurrent chromosomal copy number variations (CNVs) of autosomes in male subjects, whereas somatic loss of chromosome X was detected exclusively in female patients (17.1%). Furthermore, somatic loss of chromosome Y (LOY) was detected in about 40% of male subjects, while mosaic LOY was detected in DNA isolated from peripheral blood in 9.6% of them, and was the only recurrent CNV in constitutional DNA samples. LOY in constitutional DNA, but not in tumor DNA was associated with older age. Amongst Y-linked genes that were downregulated due to LOY, KDM5D and KDM6C epigenetic modifiers have functionally-similar X-linked homologs whose deficiency is involved in ccRCC progression. Our findings establish somatic LOY as a highly recurrent genetic defect in ccRCC that leads to downregulation of hitherto unsuspected epigenetic factors, and suggest that different mechanisms may underlie the somatic and mosaic LOY observed in tumors and peripheral blood, respectively.